2015
DOI: 10.18276/cej.2015.4-01
|View full text |Cite
|
Sign up to set email alerts
|

Running Anaerobic Sprint Test, Lactate Minimum and Critical Velocity Protocol in Shuttle Futsal Testing

Abstract: Abstract. The aims of this study were to investigate whether the running anaerobic sprint test, lactate minimum and critical velocity protocol can be applied in shuttle futsal testing, and to investigate if these protocols provide related variables. Seven male welltrained futsal players were evaluated. The lactate minimum test (Lac Min ) consisted of three phases: a) a hyperlactatemia phase using the running anaerobic sprint test (RAST); b) recovery phase; c) an incremental shuttle test for the lactate minimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
4
1
Order By: Relevance
“…Loures et al [52] reported that the anaerobic work capacity (equivalent of ADC) of soccer players under seventeen age did not correlate with power and fatigue index parameters of RAST but velocity parameters (mean and maximum velocity) had significant correlation with ADC. Similarly, it was determined a non-significant correlation between RAST and anaerobic running capacity (equivalent of ADC) in male futsal players [53]. Unlike finding of mentioned study, there was a significant correlation between all the RAST parameters and ADC (as an anaerobic parameter) in our study (table 2).…”
Section: Pedagogycontrasting
confidence: 63%
“…Loures et al [52] reported that the anaerobic work capacity (equivalent of ADC) of soccer players under seventeen age did not correlate with power and fatigue index parameters of RAST but velocity parameters (mean and maximum velocity) had significant correlation with ADC. Similarly, it was determined a non-significant correlation between RAST and anaerobic running capacity (equivalent of ADC) in male futsal players [53]. Unlike finding of mentioned study, there was a significant correlation between all the RAST parameters and ADC (as an anaerobic parameter) in our study (table 2).…”
Section: Pedagogycontrasting
confidence: 63%
“…Despite the fact that several studies followed the original 8 min recovery (Bacon and Kern, 1999; Carter et al, 1999a,b, 2000; MacIntosh et al, 2002; Dantas De Luca et al, 2003; Ribeiro et al, 2003; Zagatto et al, 2004, 2013, 2014; Simões et al, 2005, 2009; Hiyane et al, 2006; Altimari et al, 2007, 2010; Azevedo et al, 2007; Silva et al, 2007; Pardono et al, 2008; Johnson et al, 2009; Johnson and Sharpe, 2011; Mota et al, 2011; Barbieri and Gobatto, 2013; Camargo et al, 2013; Mezzaroba and Machado, 2013; Miranda et al, 2013; Miyagi et al, 2013, 2015; Campos et al, 2014; Messias et al, 2015), a myriad of recovery manipulations is also observed, especially regarding the recovery type and intensity (Davison et al, 2000; Smith et al, 2002; Rotstein et al, 2007; Silva et al, 2007; Sotero et al, 2007, 2009, 2011; Knoepfli-Lenzin and Boutellier, 2011; Vicente-Campous et al, 2014; Browne et al, 2015). Some attention has been given to this phase due to its potential LMI influence.…”
Section: Can the Lmt Be Influenced By Methodological Aspects?mentioning
confidence: 99%
“…For instance, its application was already conducted in a specific manner for taekwondo (Mota et al, 2011), basketball (Araujo et al, 2013; Camargo et al, 2013), table tennis (Barbieri and Gobatto, 2013), triathlon (Vicente-Campous et al, 2014), and futsal (Messias et al, 2015; Barbieri et al, 2017) besides several other important issues (Carter et al, 2000; Davison et al, 2000; Dantas De Luca et al, 2003; Zagatto et al, 2004, 2013; Simões et al, 2005; Rotstein et al, 2007; Mezzaroba and Machado, 2013; Miyagi et al, 2015; Sousa et al, 2017). Along with its popularity, concerns have arisen involving the influence of possible methodological aspects on LMT parameters, and effectiveness of LMI for identifying training effects or even iMLSS estimation validity.…”
Section: Theoretical Concept Of the Lmtmentioning
confidence: 99%
See 1 more Smart Citation
“…This result indicated high energy demand of anaerobic activity with a change of direction. Messias et al [30] found no significant correlation between lactate minimum speed and CV values in futsal players. The lactate value is an indicator of anaerobic endurance.…”
Section: Discussionmentioning
confidence: 91%